Dates and Honey in Nutritional Status in Pregnant Women: Systematic Review - Rezky Putri Indarwati Abdullah; Asrini Safitri; Alisa Febriana Amrin (Journal of Community Health Provision, 2026)
Optimal nutritional status during pregnancy is an important factor in supporting maternal health and fetal growth. In Islam, Thibbun Nabawi (Prophetic medicine) includes various natural food ingredients such as honey and dates, which are believed to have health benefits. The objective the research to analyze scientific evidence regarding the effect of dates and honey on the nutritional status of pregnant women based on the results of recent research. Methods: This study used a systematic review method with reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature was obtained from PubMed, Scopus, ScienceDirect, SpringerLink, Cochrane Library, and Google Scholar databases in the period January–May 2026. Articles that met the inclusion criteria were observational studies, randomized controlled trials, systematic reviews, and meta-analyses published between 2015–2025. Data were extracted and analyzed using narrative synthesis. Results showed that Thibbun Nabawi components have the potential to improve the nutritional status of pregnant women. Date consumption is associated with increased hemoglobin levels, improved energy status, and better preparation for childbirth. Honey has a positive effect on increasing energy intake and antioxidant status, and helps reduce fatigue during pregnancy. Conclusion: Dates and honey have the potential to benefit the nutritional status of pregnant women by increasing energy intake and micronutrients, antioxidant activity, and supporting maternal health. However, more robust clinical studies are needed to determine the effectiveness, optimal dosage, and safety of using various components of Thibbun Nabawi during pregnancy.